(untitled) (Journal of Ideas in Health, 2021)
Background: In the context of flattening the curve of the spread of coronavirus in Nigeria, some factors were considered. This study aimed to investigate the relationship between some of the considered factors and physical activity and investigate sex differences on physical activity during the coronavirus pandemic in Nigeria. Methods: The study was cross-sectional using an online survey and recruited participants from Nigeria’s southwest geopolitical zone through the snowball sampling technique. Descriptive statistics (such as percentages), correlation analyses, and t-test of independent measures were used to analyze the data collected. The data collection was conducted from April to June 2020. Results: The participants’ age ranges from 18 to 73years, with a mean age of 42.9 years, a median of 43years, and a standard deviation of 5.41. The result showed a significant difference between males and females (x ̅= 1001.21; SD=1371.83) on moderate physical activity during the pandemic in Nigeria. However, there was no significant relationship between contextual factors; perception of the spread [r (467) =0.028; P>0.05], fear of contracting COVID-19 [r (467) =0.041; P>0.05], stay at home measures [r (467) =-0.030; P>0.05], sensitizing others about COVID-19 [r (467) =-0.044; P>0.05], compliance with safety rules and regulations [r (467) =0.052; P>0.05] and overall physical activity. Conclusion: The study concluded that the relationship between contextual variables and physical activity among Nigerian people during the COVID-19 pandemic is not significant. Secondly, males and females are not different on vigorous and walking physical activity levels.